(untitled) (Acta Scientiarum. Animal Sciences, 2026)
The objective was to evaluate the tillering pattern in the period before and during the stockpiling of the marandu, mavuno, ipyporã and mulato II cultivars. The experimental design was completely randomized, with four replications. The tiller appearance rate (TAR) showed a similar pattern among grasses, being higher in the previous and initial stockpiling period. Among the forages, the ipyporã grass showed the highest TAR in the pre-stockpiling period. The tiller mortality rate was higher at the end of the stockpiling period. The balance between tiller appearance and mortality rates (BAL) was positive in the previous and initial stockpiling period and negative in the intermediate and final phases of stockpiling period. The BAL of the ipyporã grass was superior in the pre-stockpiling, in relation to the other grasses. The stability index showed a response pattern similar to the BAL. The number of tillers was higher in the middle, intermediate in the beginning and end, but lower in the pre-stockpiling period. The ipyporã grass has later regrowth vigor in the pre- stockpiling period. Population stability of tillers of the marandu, mavuno, ipyporã and mulato II grasses is not compromised during the stockpiling.